Pengaruh Kecepatan Pemotongan, Feed Rate Dan Depth Of Cuth Terhadap Kekasaran Permukaan Pada Benda Kerja Material S45C Pada Proses CNC Milling - Wahyu Aditiiya; Yudi Oktriadi; Zaldy Sirwansyah Suzen (Politeknik Manufaktur Negeri Bangka Belitung, 2026)
Surface quality is an important aspect in machining processes because it affects the performance and service life of components. S45C steel is widely used in the automotive and manufacturing industries, thus optimization of cutting parameters is required to obtain the best surface quality. Each machining parameter has a different level of influence on machining results. Therefore, this study was conducted to analyze the effects of cutting speed, feed rate, and depth of cut on surface roughness as well as to determine the optimum parameter combination in the CNC milling of S45C steel. The Response Surface Methodology (RSM) with a Box–Behnken design was used to develop the experimental plan consisting of 15 combinations. Surface roughness measurements were carried out using a Mitutoyo SJ-210. Analysis of variance (ANOVA) showed that depth of cut significantly affected surface roughness with a P-value < 0.05, while cutting speed and feed rate did not exhibit a statistically significant effect. The developed second-order regression model resulted in a saddle point characteristic, indicating that the optimum value was not located at either the lower or upper limit of the parameters. The optimization results indicate optimum conditions at a cutting speed of 82.85 m/min, feed rate of 298 mm/min, and depth of cut of 0.87 mm with a predicted surface roughness of 2.56 µm. These findings can serve as a reference for setting machining parameters to improve the surface quality of S45C steel.